2003
DOI: 10.1002/tcm.10047
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect ofEucommia ulmoides Oliv. on oxidative DNA damage in lymphocytes induced by H2O2

Abstract: This study used the alkaline single cell gel electrophoresis assay (comet assay) to investigate the effect of water extracts of roasted cortex and leaves from Du-zhong on DNA damage in lymphocytes induced by H(2)O(2). The results showed that the DNA damage in human lymphocytes increased with an increase in the concentration of H(2)O(2) (0-200 micro;M), but that the water extracts from Du-zhong (0-2 g l(-1)) only slightly affected DNA damage. The inhibitory effect of leaf extract on DNA damage induced by H(2)O(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Yen and Hsieh (2003) have shown that EuO leaf extract exhibited a rather significant inhibitory effect on DNA damage induced by H 2 O 2 in lymphocytes in a concentration-dependent manner. Ohmori et al (2005) assessed the antioxidant activity of EuO and found that the inhibitory effects of EuO on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals and low-density lipoprotein (LDL) oxidation were noticeable in the format of Duzhong tea in vitro.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Yen and Hsieh (2003) have shown that EuO leaf extract exhibited a rather significant inhibitory effect on DNA damage induced by H 2 O 2 in lymphocytes in a concentration-dependent manner. Ohmori et al (2005) assessed the antioxidant activity of EuO and found that the inhibitory effects of EuO on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals and low-density lipoprotein (LDL) oxidation were noticeable in the format of Duzhong tea in vitro.…”
Section: Discussionmentioning
confidence: 94%
“…Yen and Hsieh (2003) reported that the inhibitory effect of EuO leaf extract on DNA damage induced by H 2 O 2 in lymphocytes was more significant than that of roasted EuO cortex. Luo et al (2009) found that enzyme-assisted water extract is more effective than the ethanol extracts of EuO leaves for antioxidant extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to potential applications in food preservation this work has relevance also to human health, in that lipid peroxidation within the body causes membrane dysfunction and increased atherogenicity of low density lipoprotein (LDL) [6,7]. Furthermore, lipid degradation products are reported to be carcinogenic and cytotoxic [8,9]. Therefore, the use of traditional herbs with antioxidant properties has potentially valuable applications in both food and health science [10,11].…”
Section: Introductionmentioning
confidence: 97%
“…cortex extracts (EUCE) contain the same components as EU leaves, which have been the focus of medical research [2]. Studies have shown that EU leaf extracts have potent protective effects in various lipid peroxidation models and reduce oxidative damage of biomolecules [3, 811]. …”
Section: Introductionmentioning
confidence: 99%